Developing HOTS Instruments: Is It Difficult for Physics Teachers? - Saepuzaman, Duden; Retnawati, Heri; Istiyono, Edi; Haryanto, Haryanto (FKIP Universitas Lampung, 2022)
This study aims to identify the difficulties of physics teachers in making High Order Thinking Skills (HOTS).This research is phenomenological qualitative research. Data was collected through interviews, tests followed by FGD. The participants of this study were 33 physics teachers. The data were analysed using Bogdan and Biklen with reduction stages, looking for relationships between themes and conclusions. The results showed that the teacher was very familiar with HOTS. Overall, the teacher has understood the importance of HOTS and the learning process for teaching HOTS to students. But the thing that became the teacher's obstacle was assessing HOTS through an instrument that measures HOTS. If traced to the teacher's difficulties very sequential, start planning, constructing problem questions, making stimulus, combining concepts/formulas in physics, to the validation stage.Keywords: developing instruments, physics teachers' difficulty, HOTS.DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1802-1826